A Radical Proposal for Teaching, Learning, Assessment and Curriculum Development in Higher Education Computer System Development Courses for the 21st Century - Morien, Roy Irvine (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 4 (2020): October-December-2020, 2020)
The intervention of the Internet has opened up enormous possibilities in Higher Education Institutions (HEIs), as well as offering significant challenges.         This paper outlines a new regime for Teaching, Learning, Assessment and Curriculum development in computer systems development education considered more appropriate to the 21 st Century. The role of teaching academics is seen as being radically changed as implied by a new title, that of Learning Leaders, with a new set of responsibilities based around the development of on-line teaching materials, and the curating of MOOCs and other courses offered online. Students will need to shoulder significantly greater personal responsibility for their learning, but well-supported by the plethora of on-line teaching materials, allowing Anytime/Anywhere/Anydevice access to that and to the enormous universe of knowledge available on the Internet. Quality of students learning will be assured by a regime of Continuous Assessment with computer-invigilated assessment, peer-assessment, and longitudinal assessment being undertaken for formative purposes in parallel with continuous face-to-face meetings or teleconferencing with Learning Leaders acting as mentors and learning guides. Curriculum delivery will be based on a Super Project of industry-strength to take advantage of the significant benefits inherent in project-based learning plus other teaching and learning activities as appropriate with Blended Learning. Overall, the course will be conducted in an agile, iterative, collaborative manner, with inline QA. Keywords : 21 st Century Education, Agile Education, Project-Based Learning, Continuous Assessment, Leagility in Education